2009
DOI: 10.1063/1.3072789
|View full text |Cite
|
Sign up to set email alerts
|

Spin-filtering effect in the transport through a single-molecule magnet Mn12 bridged between metallic electrodes

Abstract: Electronic transport through a single-molecule magnet Mn 12 in a two-terminal set up is calculated using the non-equilibrium Green's function method in conjunction with density-functional theory.A single-molecule magnet Mn 12 is bridged between Au(111) electrodes via thiol group and alkane chains such that its magnetic easy axis is normal to the transport direction. A computed spinpolarized transmission coefficient in zero-bias reveals that resonant tunneling near the Fermi level occurs through some molecular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…Both π -π stacking and van der Waals interactions make major contributions to binding energies and therefore we include both effects by using the density functional theory (DFT) package SIESTA 24 (which compares well with other implementations of DFT [25][26][27][28][29][30][31], and a recently developed van der Waals density functional (vdW-DF), [32][33][34] which uses the revPBE35 revised version of the Perdew, Burke, and Ernzerhof generalised-gradient approximation exchange-correlation functional. 35 The vdW-DF used in SIESTA is a universal nonlocal density functional applicable to arbitrary geometries 36 and has been benchmarked recently by Carter and Rohl.…”
Section: Methodsmentioning
confidence: 99%
“…Both π -π stacking and van der Waals interactions make major contributions to binding energies and therefore we include both effects by using the density functional theory (DFT) package SIESTA 24 (which compares well with other implementations of DFT [25][26][27][28][29][30][31], and a recently developed van der Waals density functional (vdW-DF), [32][33][34] which uses the revPBE35 revised version of the Perdew, Burke, and Ernzerhof generalised-gradient approximation exchange-correlation functional. 35 The vdW-DF used in SIESTA is a universal nonlocal density functional applicable to arbitrary geometries 36 and has been benchmarked recently by Carter and Rohl.…”
Section: Methodsmentioning
confidence: 99%
“…Even though the Mn 12 is chemically bonded to the Au electrodes, the broadening of the relevant molecular orbitals is so small compared to its charging energy that the Kondo temperature is expected to be extremely low. In addition, these 14,15 and other calculations 16,17 demonstrate the importance of the internal magnetic degrees of freedom of the Mn 12 in electron transport, in contrast to typical quantum dots, regardless of the specific details of the coupling of the molecule to the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, first-principles calculations of transport through an SMM were performed on a prototype SMM Mn 12 terminated with a thiol ͑-S͒ group within Au electrodes. [14][15][16] The calculations carried out in Refs. 14 and 15 suggest that the Mn 12 molecule can function as a spin filter with low bias voltage even with nonmagnetic electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Recent systematic ab initio calculations of the freestanding binary Mo 4−x Fe x clusters in the whole range of concentrations have shown that certain isomers can be good candidates for molecular electronic devices. 18 In particular, it has been shown that the stable linear isomer of Mo 2 Fe 2 is formed by two Fe atoms separated by a nearly nonmagnetic Mo dimer.…”
Section: Introductionmentioning
confidence: 99%